Constituintes químicos de Harpochilus neesianus (Acanthaceae): isolamento direcionado por espectrômetria de massas e caracterização - Viana, Vinicius Ferreira (2022)
The second half of the 20th century brought progress in the development of synthetic medicines, but there are still obstacles that make it difficult for certain people, such as the poorest population, to have access to professional medicine and quality health care. With this, medicinal plants end up becoming the most important therapeutic source for the treatment of diseases, especially in underdeveloped countries. Harpochilus neesianus, popularly known as “cansa-cavalo” and “canudo da Caatinga”, is a species of the genus Harpochilus Nees belonging to the family Acanthaceae, endemic to the states of Rio Grande do Norte, Paraíba and Bahia in northeastern Brazil. The objective of this work was to carry out a phytochemical approach through the identification of chemical constituents isolated from Harpochilus neesianus. The aerial parts of the species were collected in the municipality of Pocinhos - PB and were submitted to the drying and pulverizing processes, later the extraction of the vegetal material was carried out through maceration, where the obtained extract was submitted to a liquid-liquid partition resulting in the hexane, chloroform, ethyl acetate and n-butanolic phases. The use of chromatographic techniques such as liquid chromatography under medium pressure (LCMP) and high performance liquid chromatography (HPLC) using the ethyl acetate phase allowed the isolation of three new compounds: brazoids E, F and G. The chromatographic techniques employed had as Silica C-18 stationary phase and methanol as mobile phase. These were identified using mass spectrometry and 1H and 13C NMR, as well as two-dimensional techniques. The results obtained in this work were of great importance for the contribution of phytochemical knowledge of the genus Harpochilus, specifically of the species Harpochilus neesianus, since it is a newly discovered genus that does not have information related to its chemical compounds.